Petrologia e tectônica do Orógeno Cauaburi ocidental: uma margem continental ativa no Orosiriano-Estateriano – região do Alto Rio Negro, noroeste do Cráton Amazônico - Túlio Amós de Araújo Mendes (2021)
Previous works defined the Cauaburi Belt (northwestern Amazon Craton), the theme of this dissertation, based on the presence of Paleoproterozoic calc-alkaline metagranitoids and orthogneisses with a subduction-related chemical signature. However, given the inherent complexity of this tectonic setting, a set of rocks and structures is expected to make up the geological framework as, with new geological data, we will approach here. The host-rocks and precursor paleobasin of the magmatic arc (Complex Taiuaçu-Cauera; 1819-1794 Ma) are high-grade metasedimentary rocks, with minor low-grade lithotypes preserved. These rocks left their chemical signature in the cordilleran magmatism (Complex Cauaburi; 1805-1759 Ma) and mostly in the crustal peraluminous metagranites (Granite Igarapé Tocandira; 1791 Ma), which were generated during the deformational/metamorphic peaks. Beyond the metagranitoids with tonalitic to syenogranitic composition of the Cauaburi Complex, the finding of mafic granofels with similar chemistry and that outcrop together with the metagranitoids brings new information about the magmatism. The basement rocks and the metagranitoids present steeply dipping E-W structures, and the parallelism of the solid-state and magmatic foliations reveals a compressional context during the metagranitoids emplacement. The dataset (field, petrographic, geochemical, and geochronological data) converges to the interpretation of a continental magmatic arc as the tectonic setting and reveals the spatiotemporal constraints on the western Cauaburi Belt tectonics. The geochronological data (U-Pb SHRIMP in zircon) show that, during the ca. 45 Mys of tectonic activity on the orogen's western sector, episodes of intense cordilleran magmatism (flare-up) were interspersed with periods of magmatic lulls and increasing deformation. In this way, the alternation of replenishment of long-lived zoned batholiths and the metamorphism/partial melting of the precursor paleobasin compose the tectonic scene. According to the Amazon Craton paleogeographic context during the Orosirian to Statherian transition, the Cauaburi Belt could be an important crustal production site of the Columbia (Nuna) Supercontinent.